Disciplining Diversity: The Roman Inquisition and Social Control in Malta, 1743–98 - Ciappara, Frans (Studies in church history, 2007)
Having lost northern Europe to the Protestants the Catholic Church tried to preserve control over what remained of the respublica Christiana. The attempt was twofold. First, it was political. The popes declared the entire Catholic world for their diocese. The government of the Christian peoples’, Pius V observed, ‘belongs to Us and We should see that they are governed with charity’. Second, the popes admitted that the Reformation had been the result partly of the religious and spiritual shortcomings of the Church itself and tried to make the requisite internal reforms. The Council of Trent defined Catholic doctrine and anathemized whoever disagreed with it. Seminaries were set up to train the clergy while the lay population was held under tight control. The Jesuits and the Office of the Holy Roman Inquisition were the main instruments of discipline. In this article I will explore the ways in which the Holy Office impinged on Maltese society during the time of the last eight inquisitors. Fortunately the archive deposits of the Inquisition in Malta are nearly complete and the recent opening of the Vatican archives has added further to our knowledge of the Maltese Holy Office.